Regular vs Boarding Schools: Uncovering Indonesian Adolescents’ Psychological Well-Being Needs and Implications for SDG 3 - Muslikah Muslikah; Abdul Kholiq; Niswatul Baroroh; Oktavia Puspita Dewi (Journal of Current Studies in SDGs, 2026)
Objective: To analyze and compare the psychological well-being of adolescents in regular and boarding schools in Indonesia. The findings are expected to provide evidence-based guidance for school counselors to identify adolescents' most urgent psychological needs and to optimize counseling services tailored to the characteristics of each school setting. Method: A quantitative study employing a cross-sectional group-comparison survey design was conducted. The participants comprised 798 adolescents, including 399 students from regular schools and 399 from boarding schools at the junior and senior high school levels. Data were collected using the Ryff Psychological Well-Being Scale (PWBS). The data were analyzed through normality testing and an independent-samples t-test to examine differences in psychological well-being between the two groups. Results: The findings revealed no significant difference in overall psychological well-being between adolescents in regular schools and those in boarding schools (p > .05). Although students in regular schools had a slightly higher mean score, the difference was not statistically significant. Descriptive analysis showed that self-acceptance was the weakest dimension among students in regular schools, whereas autonomy was the weakest dimension among students in boarding schools. Positive relationships with others represented the strongest dimension in both school types. Novelty: Extending previous research by directly comparing adolescents' psychological well-being across regular and boarding school contexts while identifying the most urgent psychological dimensions requiring intervention in each setting. The findings have practical implications for school counselors designing targeted interventions that focus on self-acceptance in regular schools and autonomy in boarding schools. These insights also offer important implications for SDG 3 (Good Health and Well-Being) by informing school-based mental health strategies that support adolescents' psychological well-being and healthy development.